2015
DOI: 10.1103/physrevb.91.155403
|View full text |Cite
|
Sign up to set email alerts
|

Probing interlayer interactions between graphene and metal substrates by supersonic rare-gas atom scattering

Abstract: We demonstrate that highly surface-sensitive supersonic rare-gas (He, Ar, and Xe) atom scattering, in both the quantum and classical regimes, can probe and quantify the interlayer interactions between graphene monolayers and metal substrates in terms of the Debye temperature corresponding to the surface normal vibration, and the surface effective mass. As models of the strongly and weakly interacting graphene, we investigated two systems, graphene on Ru(0001) and Pt (111), respectively. The experimental data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 48 publications
3
37
0
Order By: Relevance
“…A more significant difference between GIFAD and HAS lies in the ability of HAS to measure phonon modes of the graphene surface by inelastic scattering [4][5][6][7][8]. In the present case some modes specific to quasi-free standing graphene were identified [4] providing a very interesting link with dynamical behavior of the graphene layer as probed by Atomic Force Microscopy [43].…”
Section: Hcw In Gifad and Hasmentioning
confidence: 69%
See 2 more Smart Citations
“…A more significant difference between GIFAD and HAS lies in the ability of HAS to measure phonon modes of the graphene surface by inelastic scattering [4][5][6][7][8]. In the present case some modes specific to quasi-free standing graphene were identified [4] providing a very interesting link with dynamical behavior of the graphene layer as probed by Atomic Force Microscopy [43].…”
Section: Hcw In Gifad and Hasmentioning
confidence: 69%
“…On the one hand, a few meV resolution on top of few hundred eV projectiles does not seem realistic. On the other hand, Shichibe et al [8] have shown that this inelastic behavior also has specific signatures in the scattering profile perpendicular to the surface plane. Provided that topological defects are under control, these aspects could probably be investigated at grazing incidences as well.…”
Section: Hcw In Gifad and Hasmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity and dispersion relations of electronic excitations in supported graphene depend on the strength of the graphene interaction with the substrate [1][2][3][4][5][6][7][8]. Plasmonic excitations of graphene on different metallic surfaces, such as Ir(111), Cu(111) and Ni(111), have been studied in many experimental and theoretical reports [9][10][11][12][13][14][15][16][17][18][19][20]. The goal of most investigations on graphene/metal interfaces is to achieve a graphene sheet electronically decoupled from the substrate, with its electronic structure as similar as possible to the structure of free-standing graphene.…”
Section: Introductionmentioning
confidence: 99%
“…However, much quantitative analysis of diffraction intensities for beams of energy E i < 10 meV relies on elementary Debye-Waller attenuation approximations [12]. Similar approximations are used in analyzing specular helium reflection for information on graphene-metal bonding [13]. There has been progress in the calculation of diffraction intensities with explicit coupling to inelastic channels [14] and with multichannel elastic scattering theory for heavier atoms [15].…”
Section: Introductionmentioning
confidence: 99%